Pengaruh Gaya Kepemimpinan Kepala Madrasah Terhadap Kinerja Guru MIN Pecabean, Pangkah, Tegal - Masiroh ( 2052113050 ) (Prodi Pendidikan Agama Islam Program Pascasarjana STAIN Pekalongan, 2015)
Keywords : Leadership Style Principals, Teacher Performance Researching Principals Leadership Styles as a responsible person in the implementation of education at MIN or madrasah Vavorit in villagers Pecabean District of Pangkah. Has found a teacher who lacks passion in doing its job, as underperforming, will teach from the hard to find work, like teaching of the unemployed, which resulted in less successful goals to be achieved. It is caused by various factors, one of which is the lack of motivation from the headmaster to the teachers in teaching. Motivation can be seen as job in a person who is characterized by the appearance of feeling and preceded with the response to their destination. and as Principals that one of its functions as a motivator to be able to increase the motivation of the performance of teachers as subordinates. There are several ways that can be done by a leader.The way that reflects the style or type of leadership that is run. This research was conducted in MIN Pecabean, Pangkah, Tegal. Which aims to determine the effect of leadership style Madrasah head against teachers working at MIN Pecabean, Pangkah, Tegal . The variables in this study is the style of leadership Madrasah as the independent variable (X), which includes style Principals in preparing the madrasah program, creating a situation madrasah and leadership style head Mdrasah in developing the performance potential of teachers developed in education. While the teacher's performance as the dependent variable (Y). Population and sample in this study were all teachers MIN Pecabean, Pangkah, Tegal which amounted to 23 teachers. This study is a population where all populations sampled because the amount is less than 100. The purpose of this study was to determine whether there is influence headmaster leadership style on teacher performance in MIN Pecabean. To prove this hypothesis through the method of data gathering techniques used are questionnaires, interviews and documents. Test the validity of using simple linear regression techniques. While relibialitas test using Alpha techniques using SPSS V 16. Furthermore, to determine the results of the collected data calculation by using simple linear regression techniques. Results of testing the hypothesis by using simple linear regression technique with SPSS 16 statistical output that turned out to produce calculated F value of 2.845 with a P value (sign) of 1.06 is above the alpha 5% (0.05) which gives the sense that the style leadership headmaster had no impact on teacher performance, a sign that hypothesis as "influential headmaster leadership style on teacher performance" proved incapable accepted (the hypothesis is rejected). But viii by using a statistical deviation dock turns headmaster leadership style has a positive relationship with contributing positively 0.345, meaning that the better the headmaster leadership style better the performance of teachers, conversely the less well headmaster leadership style is getting less better the performance of the teacher.